Converging Islamic and religious norms in Indonesia’s state life plurality - Farkhani Farkhani; Elviandri Elviandri; Khudzaifah Dimyati; Absori Absori; Muh Zuhri (Indonesian Journal of Islam and Muslim Societies, 2022)
Indonesia is characterized by a plurality of values that inspire the formation of the state and its constitution. The democratization after the reformation made some religious communities desire to express their teachings openly. For instance, they desired to implement religious norms, resulting in laws and regional regulations with religious nuances. This study aimed to examine the convergence of Islamic norms and norms of other religions into positive law. It also intended to examine the prospects for converging these norms amid religious plurality. Using a historical and normative approach model, the practice of converging Islamic norms and norms of other religions was found from the formation to the promulgation of Law No. 1 of 1974 concerning Marriage. However, this law often receives judicial reviews, especially concerning interfaith marriages. The latest product of legislation relating to the application of religious norms into positive law is Aceh Qanun No. 6 of 2014 concerning Jinayat. The Qanun is interesting in the study of the convergence of norms of Islam and other religions in Indonesia. Although the formation and promulgation involved only followers of Islam, the Qanun accommodated the teachings of other religions. Therefore, non-Muslims prefer submitting to the Qanun rather than voting for the Criminal Code. These two examples show the prospect of converging open religious norms in various legislations.